Benefits of Lycopene in Tomatoes as a Prevention Against Atherosclerosis - Devi Meidayanti (Yayasan Pendidikan Medika Indonesia, 2021)
Atherosclerosis is damage to the artery wall which affects the two layers of the membrane, namely the intima and the media. Atherosclerosis can occur due to an increase in cholesterol levels that are not normal, resulting in accumulation of cholesterol in the blood walls, causing thickening and stiffness of the arteries. The purpose of this literature review is to discuss the benefits of lycopene in tomatoes as an antioxidant against atherosclerosis. The references used in this assessment include several articles obtained by searching the literature on the NCBI PubMed and Google Scholar in the publication range of 2005-2020. The literature search was conducted using the keywords atherosclerosis, ROS, physical activity, oxidative stress, and antioxidants. The reading sources that have been collected are then analyzed using the literature review method which includes activities, evaluation, and development of certain topics. The results of the literature review show that atherosclerosis can occur due to oxidation reactions and excessive lipids in the body of ROS can cause an imbalance between antioxidants and oxidants, resulting in oxidative stress. To prevent oxidative stress, antioxidants are needed. Antioxidants are substances that are needed by the body to ward off free radicals and prevent the damage they can cause. It is known that there are effects of active ingredients such as antioxidants which can cause atherosclerosis due to ROS.